Contribution of psychoemotional stress to the development of adaptational failure in the competitive period of qualified athletes - K. P. Bazarin; A. A. Savchenko (Acta Biomedica Scientifica, 2016)
The electroencephalography can be used to obtain objective data on the level of situational anxiety in athletes. The dynamics of the psychoemotional state of the athletes during the annual training-competitive macrocycle is characterized by the following features: in the preparatory and transition periods of the athletes the levels of anxiety and psycho-emotional stress are lower than in the control group. Competitive period is usually characterized by a significant increase in anxiety. Competitive loads experienced by athletes on the background of low anxiety lead to a less pronounced decrease in functional activity of neutrophils and activity of the antioxidant defense system.